Kecerdasan Emosi Dan Depresi Pada Mahasiswa Yang Sudah Menikah - Azizah Fitriah (Faculty of Ushuluddin and Humanities, 2018)
Every human being will one day experience a tense period in the short term when facing known problems such as career pressures, family disputes or quarrels, material pressures, and personal despair, and we will think that this is depression, which is not is an important problem because it will resolve itself, but none of these fleeting conditions is depression. Good emotional intelligence can reduce aggression, especially in adolescents. Therefore, if emotions are managed successfully, the individual will be able to entertain themselves when overwritten by sadness, can release anxiety, moodiness or offense and rise quickly again from it all. This research is field research with a correlational approach, exploring the relationship between depression and emotional intelligence in married students. The results of the hypothesis test show that between emotional intelligence and depression in married students has a significant negative relationship (XY = -0.411; sig = 0.014 <0.05). This is in accordance with the data obtained from the SPSS 19 for Windows program, stating that r table 0.334 and r xy (r hit) -0.411, said to be significant if r xy = 0.411> r table = 0.334. In other words, the higher the emotional intelligence of students who are married, the lower the possibility of depression.